Ultrasound Imaging to Estimate Carcass Quality of Pasundan Cattle based on Body Condition Score - Syifa Khairunnisa; Savitri Novelina; Nena Hilmia; Didik N Hadi; Dedi Rahmat; Mokhamad Fakhrul Ulum (Jurnal Ilmu Ternak dan Veteriner, 2021)
This research aimed to estimate carcass quality of Pasundan cattle using ultrasound imaging based on Body Condition Score (BCS). Total 31 head of female cattle with age ranging from 4 to 7 years from Regional Technical Implementation Unit of the Center for Artificial Insemination and Artificial Insemination for Beef Cattle Development at Ciamis West Java, Indonesia with BCS ranging from 1.0-4.0. The marbling score, intramuscular fat (IMF), backfat thickness (LP), and thickness musculus of m. longissimus dorsi (LD), m. psoas major (PM), m. psoas minor (PMN), m. gluteus medius (GM) and m. biceps femoris (BF) were scanned using ultrasound on 3 different locations, i.e. on 12th-13th ribs (thorax), lumbar 4th - 5th (lumbar), and between tuber coxae and tuber ischii (gluteal) with 5 MHz frequency of convex transducer. The results showed that BCS increased when LP, marbling score and IMF from m. LD, m. PM, m. PMN, and m. GM was rising. Pasundan cattle showed marbling scores ranging from score 1 to 5 and percentage IMF ranging from 2.62% to 4.82%. Body Condition Score affected carcass quality of Pasundan cattle on parameters such as musculus thickness, marbling score, and intramuscular fat (IMF) from ultrasound imaging of m. LD, m. PM. m. PMN, m. GM, and m. BF.